Corporate crime, regulation and the state - Tombs, Steve (Demystifying power, crime and social harm, 2023)
This chapter begins by acknowledging some of the remarkable achievements in Box’s contribution to the study of corporate crime. Then, by way of a sympathetic critique, it goes on to consider a presence and an absence in Box’s chapter, arguing that each is problematic and, indeed, that each of these aspects of Box’s analysis is related to the other. By the ‘presence’ I refer to Box’s discussion around how to respond to corporate crime. In my view, while this is not without merit, Box betrays some analytical tensions if not theoretical naivety - not least through his assumptions about the potential role of ‘the state and its criminal justice system’ (ibid.: 66). Thus, the absence I go on to discuss is Box’s twin failure here to address theoretically the nature of the state and what, therefore, is meant by ‘regulation’ - and both the essence and limits of this latter term. I claim that we cannot understand corporate crime without grasping its relationship to the state, not least through the nature of regulation and what it is designed to achieve. Further, these insights allow us subsequently to focus more sharply on the limits of reforms under a system of production that is dominated by corporate capital - a necessary task that Box more than glimpses but ultimately failed to follow through adequately.